2013
DOI: 10.1371/journal.pone.0075752
|View full text |Cite
|
Sign up to set email alerts
|

Silencing of Doublecortin-Like (DCL) Results in Decreased Mitochondrial Activity and Delayed Neuroblastoma Tumor Growth

Abstract: Doublecortin-like (DCL) is a microtubule-binding protein crucial for neuroblastoma (NB) cell proliferation. We have investigated whether the anti-proliferative effect of DCL knockdown is linked to reduced mitochondrial activity. We found a delay in tumor development after DCL knockdown in vivo in doxycycline-inducible NB tumor xenografts. To understand the mechanisms underlying this tumor growth retardation we performed a series of in vitro experiments in NB cell lines. DCL colocalizes with mitochondria, inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 64 publications
0
11
0
1
Order By: Relevance
“…The next day cells were transfected with FLAG-tagged human BCL2L13, a kind gift from Dr. Jürg Tschopp, Institute of Biochemistry, University of Lausanne (Kataoka et al , 2001), using Attractene (Qiagen) or empty vector and were incubated for 48 h. In the last 7 h of the incubation cells were treated with varying concentrations of KA ranging from 0–300 μM KA or vehicle 46 . Cells were treated with 250 nM MitoTracker® Red CMXRos (Invitrogen) for 5 minutes to specifically stain mitochondria 69 and fixed for 15 minutes in 4% PFA. Subsequently, cells were stained with polyclonal sheep anti-CytC (Sigma-Aldrich, 1:100) in combination with donkey anti-sheep Alexa488 (Invitrogen, 1:1000) and coverslips were mounted in vectashield mounting medium (Vector Labs).…”
Section: Methodsmentioning
confidence: 99%
“…The next day cells were transfected with FLAG-tagged human BCL2L13, a kind gift from Dr. Jürg Tschopp, Institute of Biochemistry, University of Lausanne (Kataoka et al , 2001), using Attractene (Qiagen) or empty vector and were incubated for 48 h. In the last 7 h of the incubation cells were treated with varying concentrations of KA ranging from 0–300 μM KA or vehicle 46 . Cells were treated with 250 nM MitoTracker® Red CMXRos (Invitrogen) for 5 minutes to specifically stain mitochondria 69 and fixed for 15 minutes in 4% PFA. Subsequently, cells were stained with polyclonal sheep anti-CytC (Sigma-Aldrich, 1:100) in combination with donkey anti-sheep Alexa488 (Invitrogen, 1:1000) and coverslips were mounted in vectashield mounting medium (Vector Labs).…”
Section: Methodsmentioning
confidence: 99%
“…DCX and DCLK1 are important during neurogenesis and neuronal migration (Mizuguchi et al, ; Mizuguchi et al, ; Shu et al, ; Jean et al, ; Liu et al, ; Saaltink et al, ; Shin et al, ; Verissimo et al, ; Lipka et al, ). Certain mutations that cause the neuronal migration disorder lissencephaly have been mapped to the dcx gene (Gleeson et al, ; Pilz et al, ; Gleeson et al, ; Viot et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Thereafter, investigators reported an important role of DCLK1 in dictating cognitive behavior of mice and humans 16 17 . A possible important role of DCLK1 in maintaining tumorous growths was first learned from experiments with neuroblastomas 18 19 . Only in the past 7–8 years, epithelial expression of DCLK1 was described for the first time in mouse gastric epithelial cells 20 , and the authors speculated that DCLK1 was being expressed by gastric stem cells.…”
mentioning
confidence: 99%